2020
DOI: 10.3389/fgene.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Exome Analysis Identified Novel Homozygous Splice Site Donor Alteration in NT5C2 Gene in a Saudi Family Associated With Spastic Diplegia Cerebral Palsy, Developmental Delay, and Intellectual Disability

Abstract: Hereditary spastic paraplegias (HSPs) is a rare heterogeneous group of neurodegenerative diseases, with upper and lower limb spasticity motor neuron disintegration leading to paraplegias. NT5C2 gene (OMIM: 600417) encode a hydrolase enzyme 5'-nucleotidase, cytosolic II play an important role in maintaining the balance of purine nucleotides and free nucleobases in the spinal cord and brain. In this study we have identified a large consanguineous Saudi family segregating a novel homozygous splice site donor alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In addition, skin abnormalities, epilepsy, intellectual disability, deafness, optic atrophy, peripheral neuropathy and ataxia, have been reported in association with autosomal recessive inheritance. Several mutations associated with NT5C2 in HSP type 45 have been described (Novarino et al, 2014;Darvish et al, 2017;Elsaid et al, 2017;Straussberg et al, 2017;Naseer et al, 2020). A splice mutation associated with a substantial reduction in NT5C2 level has been found in two children with severe early spasticity, mild cognitive impairment, and dysgenic and thin corpus callosum (Elsaid et al, 2017), whereas corpus callosum with normal white matter was found in their apparently normal heterozygous brother.…”
Section: '-Nucleotidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, skin abnormalities, epilepsy, intellectual disability, deafness, optic atrophy, peripheral neuropathy and ataxia, have been reported in association with autosomal recessive inheritance. Several mutations associated with NT5C2 in HSP type 45 have been described (Novarino et al, 2014;Darvish et al, 2017;Elsaid et al, 2017;Straussberg et al, 2017;Naseer et al, 2020). A splice mutation associated with a substantial reduction in NT5C2 level has been found in two children with severe early spasticity, mild cognitive impairment, and dysgenic and thin corpus callosum (Elsaid et al, 2017), whereas corpus callosum with normal white matter was found in their apparently normal heterozygous brother.…”
Section: '-Nucleotidasesmentioning
confidence: 99%
“…A 1954-bp homozygous deletion at the NT5C2 locus involving the entire coding exon 11 was identified in two siblings with HSP and intellectual disability (Darvish et al, 2017). Microcephaly has been found in two cases described by Novarino et al (2014) and Naseer et al (2020). The mechanisms underlying the clinical manifestations of NT5C2 mutations are unknown but it has been reported that NT5C2 expression is higher during fetal development and that, within the adult brain, NT5C2 is enriched in neurons compared to glial cells (Duarte et al, 2019).…”
Section: '-Nucleotidasesmentioning
confidence: 99%
“…Novarino et al . revealed that NT5C2 mutations could lead to a severe neurodegenerative motor neuron disease, hereditary spastic paraplegia (Spastic paraplegia 45, MIM #613162) ( Novarino et al, 2014 ), which was validated by other studies ( Darvish et al, 2017 ; Naseer et al, 2020 ). Collectively, it can be deduced that NT5C2 plays a crucial role in the development and functional maintenance of neurosystem.…”
Section: Discussionmentioning
confidence: 63%
“…The process through which the Aspm gene leads to microcephaly in mice is due to increasing the cell cycle duration in neural progenitors causing premature enervation of the neural progenitor pool and subsequently leading to a decrease in the upper layer of neuron production and an increase in the production at the lower end of the cortical area ( 15 ). Recently, we have reported novel mutations in genes such as SATMBP ( 17 ), MCPH1 ( 18 ); ( 19 ), WDR62 ( 20 ); ( 21 ), PGAP2 ( 22 ), and NT5C2 ( 23 ) related to microcephaly families. However, the mechanisms that explain the cause of microcephaly in humans are still unidentified.…”
Section: Introductionmentioning
confidence: 99%